2023
DOI: 10.1126/sciimmunol.ade7652
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase dissociation from mitochondria promotes oligomerization of VDAC that facilitates NLRP3 inflammasome assembly and activation

Sung Hoon Baik,
V. Krishnan Ramanujan,
Courtney Becker
et al.

Abstract: NLRP3 inflammasome activation is a highly regulated process for controlling secretion of the potent inflammatory cytokines IL-1β and IL-18 that are essential during bacterial infection, sterile inflammation, and disease, including colitis, diabetes, Alzheimer’s disease, and atherosclerosis. Diverse stimuli activate the NLRP3 inflammasome, and unifying upstream signals has been challenging to identify. Here, we report that a common upstream step in NLRP3 inflammasome activation is the dissociation of the glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 83 publications
0
24
2
Order By: Relevance
“…Additionally, in contrast to a recent report [106], we find that both hexokinase 1 and 2 (HK1, HK2) accumulate, rather than dissociate from, the mitochondria upon inflammasome stimulation (Figures 3D-E). This effect could be due to different metabolic states between cell types, particularly with NF-κB stimulation in macrophages, so it warrants further study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, in contrast to a recent report [106], we find that both hexokinase 1 and 2 (HK1, HK2) accumulate, rather than dissociate from, the mitochondria upon inflammasome stimulation (Figures 3D-E). This effect could be due to different metabolic states between cell types, particularly with NF-κB stimulation in macrophages, so it warrants further study.…”
Section: Resultscontrasting
confidence: 99%
“…Imiquimod and its derivative CL097 activate the inflammasome in part by disrupting mitochondrial and metabolic homeostasis [55][56]. Additionally, inhibition of the electron transport chain dampens NLRP3 activation by multiple agonists [56], and mitochondria have been proposed as a site of inflammasome activation [106][107][108][109]. We thus profiled how inflammasome agonists remodel the mitochondrial proteome.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we observed that the decreased catalytic activity of HK2 was associated with the increase in the levels of its cytosolic target IKBα, a regulatory protein that inhibits the nuclear translocation of NFKβ and the induction of the expression of inflammasome genes. In contrast, the complete deletion of HK2, overrode this mechanism by inducing mitochondrial dysfunction and inflammasome activation as previously described by Hu et al and others 13,15,17 .…”
Section: Introductionmentioning
confidence: 66%
“…Like other glycolytic enzymes, HK2 has non-metabolic roles that can impact inflammation independently of its canonical glycolytic role. HK2 binds to the outer mitochondrial membrane (OMM) through direct interaction with the voltage-dependent anion channel (VDAC) and its displacement induces the formation of a mitochondrial pore that triggers the activation of NLRP3 inflammasome 13 .…”
Section: Introductionmentioning
confidence: 99%
“…And the generation of ROS and M1 polarization can promote each other, leading to further exacerbation of the immune regulation. Additionally, the accumulation of mitochondrial ROS (mtROS) triggers nucleotide-binding domain and leucine-rich repeat containing receptor (NLR) family pyrin domain containing 3 (NLRP3) inflammasome activation, ultimately contributing to the maturation of the pro-inflammatory interleukin-1β (IL-1β). Hence, for the successful management of IBDs, it is imperative to meticulously design a biomaterial that can fully eradicate PAMPs, control mitochondrial dynamics, and scavenge mtROS, thus aiding the re-establishment of mitochondrial homeostasis and the easing of inflammatory reactions.…”
mentioning
confidence: 99%